1973
DOI: 10.1287/mnsc.19.8.884
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Style and the Acceptance of Management Science Recommendations

Abstract: The effective implementation of management science results depends upon a wide variety of technical and organizational factors. This paper examines the effects of cognitive style in the implementation process. Previous research in cognitive theory and implementation indicates that the nature of the researcher-manager interface may be related to measurable cognitive factors. An experimental study was conducted to investigate the influence of cognitive style and the style of written reports on the acceptance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…Kunruether and Slovic (42)]; (2) managers and students (the traditional subjects of experiments) have difficulty with simple trade-off choices [Zionts and Wallenius (77)]; (3) perceptions are selective [Dearborn and Simon (14) ] ; (4) there are clear biases and personality differences in problem-solving "styles" [Huysmans (30) , McKenney and Keen (49) , Doktor (16) ] that may even lead individuals to reject accurate and useful information [Churchman (11), Doktor and Hamilton (17)]; (5) even intelligent and experienced decision makers make many errors of logic and inference [Tversky and Kahnemann (68), Ross (61)]; and (6) managers prefer concrete and verbal data to analysis [Mintzberg (51), Stewart (65)]. …”
mentioning
confidence: 99%
“…Kunruether and Slovic (42)]; (2) managers and students (the traditional subjects of experiments) have difficulty with simple trade-off choices [Zionts and Wallenius (77)]; (3) perceptions are selective [Dearborn and Simon (14) ] ; (4) there are clear biases and personality differences in problem-solving "styles" [Huysmans (30) , McKenney and Keen (49) , Doktor (16) ] that may even lead individuals to reject accurate and useful information [Churchman (11), Doktor and Hamilton (17)]; (5) even intelligent and experienced decision makers make many errors of logic and inference [Tversky and Kahnemann (68), Ross (61)]; and (6) managers prefer concrete and verbal data to analysis [Mintzberg (51), Stewart (65)]. …”
mentioning
confidence: 99%
“…In terms of style, Doktor and Hamilton (1973) believe that decision-making is a cognitive style. Harren (1979) categorizes decision-making styles into: However, according to Thirumalai and Senthilkumar (2017), the decision making in competitive environment is more sophisticated; in addition, within the complex competitive environment, making logical decision is effected by certain circumstances.…”
Section: Ideological and Pragmatic Factorsmentioning
confidence: 99%
“…' In addition, he emphasized a preference for live action and sug gested that, whenever possible, managers engage in activities allowing such action. Further, Hysman [10], Doktor and Hamilton [5], Morris [17], and McKinney and Keen [14] have shown that personal decision style may be an effective con straint on the implementation process. The models discussed herein are formulated to be compatible with the managerial operating characteristics and to account for diffeiing decision styles.…”
Section: Focus Of the Researchmentioning
confidence: 99%
“…3 The style evaluation may give the analyst some insights into potential barriers to implementation. For example, Doktor and Hamilton [5] and Huysman [10] found that users show a preference for the mode of presentation of results. McKinnery and Keen [14] also suggest style may affect infor mation scanning as well as information processing behavior.…”
Section: A Process Modelmentioning
confidence: 99%